Effects of the addition of waxy and normal hull‐less barley flours on the farinograph and pasting properties of composite flours and on the nutritional value, textural qualities, and in vitro digestibility of resultant breads. Issue 10 (28th August 2020) - Liu, Juan; Li, Qiao; Zhai, Huisheng; Zhang, Yuhong; Zeng, Xingquan; Tang, Yawei; Tashi, Nyima; Pan, Zhifen
Abstract : Abstract: Hull‐less barley (HLB), especially waxy HLB, contains many physiologically active ingredients; however, its poor processing performance and end‐product quality are unfavorable. In this study, 80% waxy or normal HLB wholegrain flour (WGF) and 20% wheat flour were used for baking bread. The farinograph and pasting properties of composite powders, and the nutritional value, textural properties, and in vitro hydrolysis of resultant breads were evaluated. The addition of a high proportion of HLB WGFs significantly increased the nutritional value of breads, especially the β‐glucan contents of waxy HLB breads. The addition of HLB WGFs and a suitable amount of wheat gluten led to a lower degree of softening of HLB bread flours but improved its farinograph characteristics, such as higher water absorption rate, development time, stability time, and farinograph quality number. Although the sensory profiles of HLB breads were considerably lower than those of wheat bread, they still received a good overall acceptability from a panel of sensory evaluators. HLB breads, particularly the waxy types, exhibited higher hardness, gumminess, chewiness, and lower specific volume, glycemic index and equilibrium concentration in starch hydrolysis. After baking, the starch crystallinity of dough changed from A to V type, and the relative crystallinity decreased. Overall, waxy HLB breads had more nutritional value than normal HLB breads. Higher β‐glucan and total dietary fiber content in HLB might have a positive effect on the nutritional value of the resultant breads. However, high β‐glucan and total dietary fiber was also accompanied by a negative effect on the sensory quality and processing performance of the end product. Practical Application: The composite flour with 80 g hull‐less barley wholegrain flour, 20 g wheat flour, and 30 g wheat gluten can be substituted in breadmaking. Compared to wheat bread, hull‐less barley bread exhibited different but acceptable sensory properties and had more nutritional value, particularly the waxy one. Therefore, a high proportion of hull‐less barley could be recommended for bread production.